Influences of career establishment strategies on generation Y’s self-directedness career: can gender make a difference? - Wong, Siew Chin; Mohd Rasdi, Roziah (Emerald Group Publishing, 2019)
Purpose – The purpose of this paper is to examine the influence of generation Y’s career establishment strategies on self-directedness career and to determine the moderation effect of gender on the relationship. Design/methodology/approach – Data were collected from 188 full-time employees from different functional areas and departments of selected MNCs in Malaysian Electrical and Electronic Industry. Partial least squares structural equation modeling was used to examine the influences of establishment strategies and the moderating role of gender on self-directedness career. Findings – Findings show that there are significant positive relationship between career strategies and selfdirectedness career at career establishment stages of generation Y. There is a significant difference between males and females in career establishment strategy (i.e. creating career opportunities) and self-directedness career. Research limitations/implications – This paper explains self-directedness career based on the review of related career literatures whereby some may not specifically referring to Generation Y. Practical implications – Such insights are useful for HRD practitioners dto develop relevant HRD interventions to assist individuals and organizations in career development. Originality/value – This paper offers new insight into the predictors of self-directedness career and the moderating role of gender on the relationships.